Mentoring MSMEs through E-Promotion as A Rebranding Strategy Based on Local Wisdom - Ning Karnawijaya; Lila Pangestu Hadiningrum; Siti Rokhaniyah; Indri Pujiastuti (UNUSA Press, 2022)
The pandemic affects Micro, Small, and Medium Enterprises (MSMEs) as an economic sub-sector. MSMEs products have marketing problems, so many unsold products. Traditional marketing strategies can not reach a vast market share, so income significantly declined during the Covid-19 pandemic. In Kejuron Ward, Taman District, the Madiun City, MSMEs actors consist of several industrial sectors such as food and clothing sales. During the COVID-19 pandemic, MSMEs actors in the Kejuron Ward tried to use alternatives to online selling. However, promotions in online selling were still not optimal to attract customers as offline promotions. The target issues were a lack of knowledge in digital marketing and less attractive products. Mentoring MSMEs through e-promotion as a rebranding strategy based on local wisdom was an effort to overcome the partners' problems. The empowerment model used in this community service was participatory assistance through lectures, discussions, and practices methods. There were significant differences in success indicators before and after socialization and practice regarding e-promotion as a local wisdom-based rebranding strategy. The most significant increase was knowledge levels which improved by 50% after the socialization. Thus, this community service could increase innovation and creativity in the target community and solve MSMEs' business problems in Kejuron Ward. In conclusion, mentoring MSMEs through e-promotion as a rebranding strategy based on local wisdom increases partners' knowledge in digital marketing, more attractive products packaging, and updated MSMEs' products with trending products. There should be ongoing assistance and communication to support the sustainability of this program